Artikel Review : Bahan Penghancur Tablet - Maya Shifa; Maria Fransiska Silviani; Fina Nikmatul Wasi’ah; Windi Tri Wahyuni; Niken Rahmita Khairani; Sari Fatul Layly; Tiara Putri Hartanto; Maulidiyah Cholifah; Dewi Rahmawati (STIKes Ibnu Sina Ajibarang, 2024)
Tablets are solid preparations that contain medicinal ingredients with or without fillers. The addition of disintegrating materials aims to counter the pressure during tablet manufacturing, especially in the process of releasing the tablet dosage form which begins with the disintegration process. In this analysis, the method used is based on a literature review from electronic data sources. Based on the literature results, starch can act as a crushing agent because the granules are able to expand when in contact with water and amylose is a component that has the properties of a crushing agent because of its ability to expand. It can be concluded that starch or starch from any plant is effective as a tablet disintegrating agent not only because of its good water contact ability, but if we look at the evaluation tests produced, almost all of them meet the requirements.